Are Training Programs More Effective When Unemployment Is High? - Lechner, Michael; Wunsch, Conny (Journal of Labor Economics, 2009)
We estimate short‐run, medium‐run, and long‐run individual labor market effects of training programs for the unemployed by following program participation on a monthly basis over a 10‐year period. Since analyzing the effectiveness of training over such a long period is impossible with experimental data, we use an administrative database compiled for evaluating German training programs. Based on matching estimation adapted to address the various issues that arise in this particular context, we find a clear positive relation between the effectiveness of the programs and the unemployment rate over time.